Documentation and Coding Education in Emergency Medicine Residency Programs: A National Survey of Residents and Program Directors - Pines, Jesse M. (California Chapter of the American Academy of Emergency Medicine, 2004)
PURPOSES: To assess attitudes and practices of documentation and coding education for emergency medicine residents (EMRs). METHODS: Questions regarding documentation teaching methods were formulated into online surveys for program directors (PDs) and EMRs. RESULTS: Fifty-three of 104 PDs and 446 of 576 EMRs who received the survey completed it. Although 93% of EMRs and 63% of PDs believe proper chart documentation is an important skill, only 18% of EMRs and 25% of PDs believe their program’s teaching was adequate. Eleven percent of EMRs reported that they were comfortable with their knowledge of documentation. EMRs who received formal lectures and feedback reported higher comfort levels with their knowledge of documentation (3.3 ± 1.1 vs. 4.5 ± 1.4, p < 0.05) than those who did not receive formal lectures and feedback. CONCLUSIONS: Although most physicians who were surveyed agreed that documentation and coding is a vital skill, many EMRs and PDs report inadequate instruction. Resident education may benefit from broader implementation of formal lectures and formal feedback on documentation and coding skills.